PENGARUH STRATEGIC AGILITY TERHADAP ORGANIZATIONAL PERFORMANCE MELALUI MEDIASI INNOVATION CAPABILITY DI BPVP PANGKEP - Hartanto Hartanto; Mochamad Sarif Hasim (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The aim of this research is to identify and analyze the influence of strategic agility variables on organizational performance which is mediated by innovation capability at BPVP Pangkep. A quantitative approach was used in this research. Supported by descriptive analysis and path analysis methods. The sampling of 47 employees as respondents was carried out using a saturated sampling technique or non-probability sampling method. Data collection was carried out by distributing questionnaires. The data results are then processed and analyzed using statistical tests, such as the t test which functions to test the hypothesis and followed by the Sobell test to determine the ability of the intervening variable to mediate. Previously, data quality testing was carried out through validity and reliability tests. The resulting research resulted in the conclusion that (1) strategic agility has a positive effect on organizational performance, (2) strategic agility has a positive effect on innovation capability, (3) innovation capability has a positive effect on organizational performance, and (4) innovation capability has a mediating effect on the relationship between strategic agility and organizational performance.